Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 110875 by bemath last updated on 31/Aug/20

(1)∫_e ^e^e   ((ln (x).ln (ln (x)))/x) dx ?  (2)lim_(x→π/4)  ((cosec^2 x−2)/(cot x−1))  (3) Given  { ((xy=((16y−9x)/(45)))),(((4/( (√x)))−(3/( (√y))) = 5)) :}  ⇒find 9(√(xy))

(1)eeeln(x).ln(ln(x))xdx?(2)limxπ/4cosec2x2cotx1(3)Given{xy=16y9x454x3y=5find9xy

Answered by Dwaipayan Shikari last updated on 31/Aug/20

∫_e ^e^e  ((log(x)log(log(x)))/x)dx   (logx=t,(1/x)=(dt/dx))  ∫_1 ^e tlog(t)dt  [logt.(t^2 /2)]_1 ^e −∫_1 ^e (t/2)=(e^2 /2)−(e^2 /4)+(1/4)=(1/4)(e^2 +1)

eeelog(x)log(log(x))xdx(logx=t,1x=dtdx)1etlog(t)dt[logt.t22]1e1et2=e22e24+14=14(e2+1)

Commented by bemath last updated on 31/Aug/20

thank you sir.

thankyousir.

Commented by bemath last updated on 31/Aug/20

Answered by Dwaipayan Shikari last updated on 31/Aug/20

2)lim_(x→(π/4)) ((1−2sin^2 x)/(sin^2 x(cosx−sinx))).sinx=lim_(x→(π/4)) ((cos^2 x−sin^2 x)/(sinx(cosx−sinx)))=(√2).(sinx+cosx)  =2

2)limxπ412sin2xsin2x(cosxsinx).sinx=limxπ4cos2xsin2xsinx(cosxsinx)=2.(sinx+cosx)=2

Commented by bemath last updated on 31/Aug/20

Answered by bobhans last updated on 31/Aug/20

(3)  { ((45=((16y−9x)/(xy))=((16)/x)−(9/9)=((4/( (√x))))^2 −((3/( (√y))))^2 )),(((4/( (√x)))−(3/( (√y))) = 5)) :}   { ((45=((4/( (√x)))−(3/( (√y))))((4/( (√x)))+(3/( (√y))))...(i))),((5=(4/( (√x)))−(3/( (√y)))...(ii))) :}  ⇔ 45 = 5((4/( (√x)))+(3/( (√y)))) ; (4/( (√x)))+(3/( (√y))) = 9...(iii)  (i)+(iii)⇒ (8/( (√x))) = 14⇒(√x) = (4/7) and (3/( (√y)))=9−7  (√y) = (3/2). therefore 9(√(xy)) = 9×(4/7)×(3/2)  = ((54)/7)

(3){45=16y9xxy=16x99=(4x)2(3y)24x3y=5{45=(4x3y)(4x+3y)...(i)5=4x3y...(ii)45=5(4x+3y);4x+3y=9...(iii)(i)+(iii)8x=14x=47and3y=97y=32.therefore9xy=9×47×32=547

Commented by bemath last updated on 31/Aug/20

thank you

thankyou

Answered by mathmax by abdo last updated on 31/Aug/20

I =∫_e ^e^e   ((ln(x)ln(lnx))/x) dx  changement lnx =t give  I =∫_1 ^e  ((t ln(t))/e^t ) e^t  dt =∫_1 ^e  tln(t)dt =[(t^2 /2)ln(t)]_1 ^e −∫_1 ^e (t^2 /2)(dt/t)  =(e^2 /2) −(1/2)∫_1 ^e  t dt =(e^2 /2)−(1/2)[(t^2 /2)]_1 ^e  =(e^2 /2)−(1/4){e^2 −1} =(e^2 /4) +(1/4) ⇒  I =((1+e^2 )/4)

I=eeeln(x)ln(lnx)xdxchangementlnx=tgiveI=1etln(t)etetdt=1etln(t)dt=[t22ln(t)]1e1et22dtt=e22121etdt=e2212[t22]1e=e2214{e21}=e24+14I=1+e24

Terms of Service

Privacy Policy

Contact: info@tinkutara.com